Masih Relevankan Pembelajaran Ekpositori Saat Ini? Potret Pembelajaran Matematika Pada Salah Satu SMA Di Kota Bandung - Eka Chandra, Fitriana (Universitas Islam Jember, 2024)
As time goes by, many innovative approaches, strategies, methods, and learning techniques have been created to make students more interested in learning mathematics. However, in reality, not all teachers can apply various innovative student-centered learning approaches in mathematics learning. This research took place at a high school in the city of Bandung to describe how mathematics learning using the expository method is implemented in that school. This research is case study research, with data collected using observation and interview techniques with both teachers and students. Based on the results of observations, it is known that learning is carried out in three stages, namely preliminary, core, and closing activities. In the core learning activities, the teacher chooses to use the expository method which collaborates with cooperative learning and constructivist learning, although in this case, expository learning is more dominant. Learning mathematics using the expository method is seen as more effective for use in learning because it suits the character of the students and the material being taught. Keywords: Expository, Mathematics